2015
DOI: 10.1021/acsami.5b07260
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Amyloid-β Fibrils into Mature Microrod-Shaped Structure by Histidine Functionalized Water-Soluble Perylene Diimide

Abstract: Alzheimer's disease (AD) is associated with different types of amyloid peptide aggregates including senile plaques, fibrils, protofibrils, and oligomers. Due to these difficulties, a powerful strategy is needed for the disaggregation of amyloid aggregates by modulating their self-aggregation behavior. Herein, we report a unique approach toward transforming the aggregated amyloidogenic peptides using an amino acid functionalized perylene diimide as a molecular modulator, which is a different nondestructive appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Thioflavin T (ThT) assay is one of the most widely used methods to identify A β aggregates with high sensitivity . The emission band at 450 nm is expected to be directly proportional to the amount of A β aggregates present; consequently, the formation of A β aggregates can be easily followed by measuring ThT fluorescence enhancement by organic molecules in concentration‐dependent manner . To investigate the effect of the synthesized analogs on A β aggregation, compound 4m (0.02, 0.06, 0.1 m m ), which showed good activity in former tests, and galantamine were selected to perform thioflavin T (ThT) assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thioflavin T (ThT) assay is one of the most widely used methods to identify A β aggregates with high sensitivity . The emission band at 450 nm is expected to be directly proportional to the amount of A β aggregates present; consequently, the formation of A β aggregates can be easily followed by measuring ThT fluorescence enhancement by organic molecules in concentration‐dependent manner . To investigate the effect of the synthesized analogs on A β aggregation, compound 4m (0.02, 0.06, 0.1 m m ), which showed good activity in former tests, and galantamine were selected to perform thioflavin T (ThT) assay.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the cytotoxicity of these peptides, two kinds of strategies, that is, inhibiting aggregation and disassembling aggregates of amyloid peptides by a variety of designed molecules such as peptides, antibodies, metal ion chelators, small molecules, and nano particles are applied . Currently, smart self‐assembling molecules have been identified that associate and promote the peptide–peptide and peptide–organic interactions converting the A β monomers and oligomers into non‐toxic forms, which is a different non‐destructive approach as compared to inhibiting the aggregation of peptides .…”
mentioning
confidence: 99%
“…Furthermore, another study has demonstrated the stability, phototoxicity and biocompatibility of PDI–[ARGD] 2 symmetrical derivatives, suggesting potential usage in the field of photodynamic therapy [ 46 ]. Finally, a biocompatible PDI[H] 2 probe was described as a unique system towards the modulation of the amyloid fibril formation process [ 88 ]. This probe co-assembled with amyloid-β peptide (Aβ), which is associated with Alzheimer’s disease, via H-bonding that led to the enhancement of the π−π interactions between Aβ and PDI–[H] 2 .…”
Section: Potential Applications Of Pdi Bioconjugatesmentioning
confidence: 99%
“…This interaction accelerated the aggregation process of Aβ into large micron-sized co-assembled structures. Since the oligomeric forms of amyloidogenic peptides are reported to have higher toxicity as compared to the fibrillar aggregates [ 89 , 90 ], these PDI conjugates could lead to potential design and development of drugs targeted toward Alzheimer’s disease treatment [ 88 ].…”
Section: Potential Applications Of Pdi Bioconjugatesmentioning
confidence: 99%
“…Changes in PL intensity, emission wavelength, anisotropy, and lifetime due to the presence of Aβ aggregates have been explored for the study of amyloid aggregation. In order to make use of this assortment of properties, a variety of probes have been developed including, among others, Thioflavin T (ThT), [5–6] Congo Red (CR), [7–10] Carbazoles, [11–13] Perylenes, [14,15] and their derivatives. In addition to traditional organic dyes, in the last decade, photoluminescent metal complexes have been added to the toolbox for amyloid detection.…”
Section: Introductionmentioning
confidence: 99%